All-trans retinoic acid (ATRA) reduces proliferative capacity and Brachyury levels in the chordoma cell line UCH-1. (28th September 2020) - Michaelis, Martin; Robinson, Helena; McFarlane, Ramsay J.; Wakeman, Jane A.
Abstract: Chordoma is a rare bone cancer for which there are no approved drugs. Surgery is the principle treatment but complete resection can be challenging due to the location of the tumours in the spine and therefore finding an effective drug treatment is a pressing unmet clinical need. A major recent study identified the transcription factor Brachyury as the primary vulnerability and drug target in chordoma. Previously, all-trans retinoic acid (ATRA) has been shown to negatively influence expression of the Brachyury gene, TBXT. Here we extend this finding and demonstrate that ATRA lowers Brachyury protein levels in chordoma cells and reduces proliferation of the chordoma cell line U-CH1 as well as causing loss of distinctive chordoma cell morphology. ATRA is available as a generic drug and is the first line treatment for acute promyelocytic leukaemia (APL). This study implies ATRA could have therapeutic value if repurposed for chordoma.